PENGUKURAN DAN PENILAIAN BIAYA KUALITAS DALAM UPAYA PENGENDALIAN KUALITAS PRODUK - Rumanintya Lisaria Putri (Fakultas Ekonomi Universitas 45 Surabaya, 2016)
Quality costs (cost of quality) is the costs arising from the results of a bad product quality. Quality costs are costs associated with the creation, identification, repair and damage prevention. The aim of research to determine the measurement and reporting of quality costs, to be used as a means of cost control and to determine the quality of information from the measurement and reporting of quality costs to be used as a means of controlling the cost of quality in Guyub Santoso UD Blitar. This type of research used in this research is descriptive (descriptive research) Performance report quality costs trend one year from 2012 to 2013 illustrates that the actual quality costs that occurred in 2012 and 2013 amounted Rp.590.245.500,00 and Rp.538.396.500,00, indicating favorable variant in which a decline of Rp.50.849.000,00. Performance report quality costs trend one year from 2013 to 2014 illustrates that the actual quality costs that occurred in 2013 and 2014 amounted Rp.538.396.500.,00 and Rp. 466,431,000.00 showed favorable variant in which a decline of Rp.72.765.500,00 or 13.51%. Measurement of the percentage fees based on the actual quality of the previous period showed adverse variance in abatement costs increased by Rp.72.765.500,00 (13.51%), but the number is still smaller when compared with a decrease of the cost categories of losses on low quality (internal failure costs) where there is a favorable variant of Rp 79,682,500.00 or 31.5%. The results of the overall study, a decrease in total quality costs amounted to 8.61% for the year 2012 to the year 2013 and 13.34% for the years 2013 to 2014. It shows that the cost of quality control conducted by UD Guyub Santoso Blitar been successful in controlling costs relating to the quality, so as to achieve cost efficiencies from year to year, but the conditions should be analyzed further for further analysis can assist management to plan the development and quality control in the years to come.